Analisis Kualitas Pelayanan terhadap Tingkat Kepuasan Pelanggan pada Stasiun Pengisian Bahan Bakar Umum: Studi Kasus SPBU 64.752.02 - Yolla Depriany Rimba Panggalo; La Ode Ahmad Safar Tosungku; Lina Dianati Fathimahhayati (Operations Excellence: Journal of Applied Industrial Engineering, 2022)
One of the public fuel filling stations that is still operating in Samarinda City, East Kalimantan is SPBU 64,752.02 which is located on Jalan Bung Tomo, Sungai Keledang Village, Samarinda Seberang District, Samarinda City, East Kalimantan Province. The road is the main road between cities. The gas station located on the road is classified as crowded, therefore there are many repeated complaints against the services provided, such as the availability of running out of fuel, the cleanliness of the available facilities, to the operator's actions in serving customers. The purpose of this study is to provide results of service quality analysis and proposed improvements to service quality where there are still negative gaps. The method used in determining service quality is the Fuzzy Servqual method based on the dimensions of reliability, responsiveness, assurance, empathy, and tangibles. From the results of this study, the quality of service at the gas station 64,752.02 based on the Fuzzy Servqual method, it was found that the overall attribute statements used in the study had a negative value. Complaints submitted by customers are an important attribute that needs to be improved because the gap between expectations and reality received by customers has not been met by the gas station. The improvement proposal given in this research is expected to increase customer satisfaction if it is implemented with an effective strategy.